Study and Application of Information Management System for In-Service Inspection of Nuclear Power Plant - Xueliang Zhang; Yancheng Fan; Chunyang Wang; Guozheng Zhou (Dianxin kexue)
Based on summarizing of traditional in-service inspection（ISI）management mode，the ISI management system was studied and developed.Realization of NPP ISI informational management was achieved.Due to the application of the management system，problems existed in traditional management mode were solved，ISI management efficiency and management capacity of NPP were significantly improved.Future application of the ISI management system can provide strong help for realization of specialization，standardization，intensive and multi-base-multi-units management of NPP ISI.